Development and Reliability Testing of a Health Action Process Approach Inventory for Physical Activity Participation among Individuals with Schizophrenia - Arbour-Nicitopoulos, Kelly P.; Duncan, Markus; Remington, Gary; Cairney, John; Faulkner, Guy E. (Frontiers in Psychiatry, 2014)
Individuals with schizophrenia tend to have high levels of cardiovascular disease and lower physical activity (PA) levels than the general population. Research is urgently required in developing evidence-based behavioral interventions for increasing PA in this population. One model that has been increasingly used to understand the mechanisms underlying PA is the Health Action Process Approach (HAPA). The purpose of this study was to adapt and pilot-test a HAPA-based inventory that reliably captures salient, modifiable PA determinants for individuals with schizophrenia. Initially, twelve outpatients with schizophrenia reviewed the inventory and provided verbal feedback regarding comprehension, item relevance, and potential new content. A content analysis framework was used to inform modifications to the inventory. The resultant inventory underwent a quantitative assessment of internal consistency and test-retest reliability. Twenty-five outpatients (Mage= 41.5 ± 13.5 years; 64% male) completed the inventory on two separate occasions, one week apart. All but two scales showed good internal consistency (Cronbach’s α=0.62–0.98) and test-retest correlations (rs = .21-.96). Preliminary assessment of criterion validity of the HAPA inventory showed significant, large-sized correlations between behavioural intentions and both affective outcome expectancies and task self-efficacy, and small-to-moderate correlations between self-reported minutes of moderate-to-vigorous PA and the volitional constructs of the HAPA model. These findings provide preliminary support for the reliability and validity of the first-ever inventory for examining theory-based predictors of moderate to vigorous PA intentions and behavior among individuals with schizophrenia. Further validation research with this inventory using an objective measure of PA behavior will provide additional support for its psychometric properties within the schizophrenia population.